2017
DOI: 10.1007/164_2017_76
|View full text |Cite|
|
Sign up to set email alerts
|

Presynaptic Ethanol Actions: Potential Roles in Ethanol Seeking

Abstract: Ethanol produces intoxication through actions on numerous molecular and cellular targets. Adaptations involving these and other targets contribute to chronic drug actions that underlie continued and problematic drinking. Among the mechanisms involved in these ethanol actions are alterations in presynaptic mechanisms of synaptic transmission, including presynaptic protein function and excitation-secretion coupling. At synapses in the central nervous system (CNS), excitation-secretion coupling involves ion chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 151 publications
0
13
0
Order By: Relevance
“…While there have been conflicting reports 29 , it has been suggested that low alcohol concentrations influence the activity of δ-containing GABA A receptors in recombinant receptor systems as well as in slices 911,30,31 . However, it is also likely that the well-documented effects of ethanol on presynaptic GABA release 1517 and/or increases in neurosteroid levels 18–20,32 may indirectly mediate the effects of ethanol on these receptors. Regardless, global deletion of the Gabrd gene was found to be associated with reduced 24 hr alcohol consumption and preference in males and females 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been conflicting reports 29 , it has been suggested that low alcohol concentrations influence the activity of δ-containing GABA A receptors in recombinant receptor systems as well as in slices 911,30,31 . However, it is also likely that the well-documented effects of ethanol on presynaptic GABA release 1517 and/or increases in neurosteroid levels 18–20,32 may indirectly mediate the effects of ethanol on these receptors. Regardless, global deletion of the Gabrd gene was found to be associated with reduced 24 hr alcohol consumption and preference in males and females 12 .…”
Section: Discussionmentioning
confidence: 99%
“…GABA receptors containing the γ2 subunit, which mediate phasic inhibition, respond to high alcohol concentrations; whereas, δ-containing GABA A receptors, which mediate tonic inhibition, have been suggested to respond to low/moderate alcohol concentrations 1113 . The role of extrasynaptic GABA A Rs in conferring sensitivity to alcohol has been proposed to be due to direct effects on these receptors 14 , but may also be mediated indirectly via changes in presynaptic GABA release 1517 or ethanol-induced increases in neurosteroids 18–20 that potentiate the effects of GABA on these extrasynaptic receptor subtypes 21 . Whether the δ subunit is necessary for the behavioral effects of alcohol concentrations achieved in an active binge drinking session remains unknown, although the global loss of these receptors has been shown to reduce alcohol intake and alcohol preference 12 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Acutely, alcohol promotes GABA release and may also reduce GABA degradation, producing sedative and anxiolytic effects. 21 Chronic alcohol use leads to a decrease in the number of GABA A receptors. Clinically, this downregulation manifests as tolerance to alcohol's sedating effects.…”
Section: Modesto-lowe and Colleagues ■ Alcohol's Actionsmentioning
confidence: 99%
“…Clinically, this downregulation manifests as tolerance to alcohol's sedating effects. 21 Alcohol affects the signaling of glutamatergic interaction with the N-methyl-d-aspartate (NMDA) receptor. 22 Glutamate activates this receptor as well as the voltage-gated ion channels, modifying calcium infl ux and increasing neuronal excitability.…”
Section: Modesto-lowe and Colleagues ■ Alcohol's Actionsmentioning
confidence: 99%
“…For example, loss of endocannabinoid-dependent LTD is observed following exposure to several drugs in addition to ethanol (Mato et al 2005;Xia et al 2006;Adermark et al 2011;Atwood et al 2014a). However, the mechanisms underlying these effects are likely to be different, as cannabinoid drugs down-regulate receptor function, while EtOH may have a more general effect on intraterminal signaling mechanisms involved in presynaptic LTD (Hoffman et al 2003;Mato et al 2005;Lovinger 2017). Given the different primary molecular targets of ethanol and other drugs of abuse, it is likely that compensatory plasticity involving changes in these target molecules would also differ for the different substances.…”
Section: Future Directionsmentioning
confidence: 99%